Thinking, Consciousness and Ability in the Construction of University Discipline Service Ecology - Luo Xinghua (SHS Web of Conferences, 2023)
Based on the discipline service of the library, this paper studies the composition of the discipline service ecology of universities, and believes that the discipline service ecology of universities is a dynamic and open system. It is proposed that building a healthy and harmonious discipline service ecology is the basis for universities to continue to carry out discipline services. It also analyzes the thinking, consciousness and ability necessary for building a good discipline service ecology, and makes a theoretical discussion for the creative development of discipline service.